2006
DOI: 10.1002/cncr.21792
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine improves patient outcomes in myelodysplastic syndromes

Abstract: BACKGROUNDAberrant DNA methylation, which results in leukemogenesis, is frequent in patients with myelodysplastic syndromes (MDS) and is a potential target for pharmacologic therapy. Decitabine indirectly depletes methylcytosine and causes hypomethylation of target gene promoters.METHODSA total of 170 patients with MDS were randomized to receive either decitabine at a dose of 15 mg/m2 given intravenously over 3 hours every 8 hours for 3 days (at a dose of 135 mg/m2 per course) and repeated every 6 weeks, or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
1,009
2
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,393 publications
(1,055 citation statements)
references
References 94 publications
(107 reference statements)
27
1,009
2
17
Order By: Relevance
“…This-at first counterintuitive-clinical finding was confirmed in MDS [27,28] and AML [7,8]. While these trials were ongoing, Breems et al [23] first described the novel cytogenetic poor-risk category of MK in AML.…”
Section: Discussionmentioning
confidence: 92%
“…This-at first counterintuitive-clinical finding was confirmed in MDS [27,28] and AML [7,8]. While these trials were ongoing, Breems et al [23] first described the novel cytogenetic poor-risk category of MK in AML.…”
Section: Discussionmentioning
confidence: 92%
“…The earliest clinical data of HMAs in AML patients were noncomparative trials mostly involving individuals unfit for IC [17][18][19][20]25]. Next, subgroup analyses of large prospective phase III trials of Aza or Dec demonstrated superior outcomes for HMA over best supportive care in AML patients with marrow blast counts of 20-30% [21,30,33]. HMA have subsequently been evaluated in multiple trials for elderly AML patients with more aggressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…5-Azacytidine and decitabine have shown significant clinical benefit in the treatment of myelodysplastic syndrome (Silverman et al, 2002;Kantarjian et al, 2006) and are also used for the treatment of myeloid leukemias. Both drugs are particularly effective when administered at low doses, which are sometimes below 10% of their maximum tolerated doses (Issa and Kantarjian, 2009).…”
Section: Introductionmentioning
confidence: 99%